194 Libido and semen quality in intact and altered (short scrotum and castrated) post-pubertal male dairy sheep lambs. (29th July 2019) - O'Brien, Dahlia; Wildeus, Stephan; Schoenian, Susan; Semler, Jeff; David, Gordon; Bennett, Mary Beth; Anderson, Chris; Travis, Ashley
Abstract: Short-scrotum (induced cryptorchid) rams can retain growth and performance characteristics of intact-rams while making them sterile and facilitating co-grazing with ewe-lambs. East Friesian x Lacaune male lambs left intact (n = 19; IN), rendered short-scrotum (n = 17; SS) or neutered (n = 25; WE) by 10 d of age, were used to evaluate libido and semen quality at 7-mo old. Lambs were managed as one group on a forage-based diet supplemented with a grain mixture (barley and soybean meal at 0.7 kg/d). Four CIDR-treated estrus-induced ewes were placed two/pen in adjacent 2.5x2.5 m pens for libido testing. Males were introduced individually to ewe pens for 5 min and reproductive behaviors recorded (anogenital sniffs, foreleg kicks, flehmen, false mounts, and service). Semen was collected from 6 random IN and SS lambs via artificial vaginas using estrus-induced ewes as teasers. Volume was recorded, and ejaculate extended in milk/egg yolk, packaged into straws, and stored at 5°C for analysis with a CASA system the following day. Behavior measurements were compared between types using PROC GLM. Ejaculate characteristics are presented as mean±SD due to insufficient sperm concentrations of SS ejaculates. Anogential sniffs, foreleg kicks, and mounts were similar in IN and SS, and higher (P < 0.05) than in WE (7.44 and 6.34 vs. 4.76; 1.72 and 1.60 vs. 0.17; 1.78 and 2.05 vs. 0.22; respectively). Number of services were higher (P < 0.001) in IN than SS (1.11 vs. 0.53), but time to service (112 sec) was not different. Ejaculate volume was similar in IN and SS (0.51 mL), but SS ejaculates were essentially devoid of sperm. Ejaculates from IN lambs had 0.69x109±0.48 x10 9 sperm, with 68.9±12.5% progressive motility, 81.8±6.1% viability and 87.1±6.1% morphologic normality. Ram lambs rendered short-scrotum by 10 d of age had reproductive behavior similar to intact post-pubertal rams, but ejaculate characteristics showed them to be sterile